A study of the fundamental solutions of equations by means of mathematical analysis methods in aggressive environments - Babadjanova, V. G. (Національний технічний університет "Харківський політехнічний інститут", 2026)
The study of processes occurring in aggressive environments solely through experimental methods is often costly and not always feasible. Therefore, the development of mathematical models and the derivation of fundamental solutions hold significant scientific and practical importance. Mathematical analysis provides the primary methodological framework for this field, enabling the investigation of essential system properties such as boundedness, convergence, stability, and uniqueness. This work presents an examination of the fundamental solutions of differential equations formulated for aggressive environments using advanced methods of mathematical analysis.
Keywords: study; equations; mathematical analysis; methods; aggressive environments; materials science; modeling; scientific research; corroding materials